Actinide arene-metalates: ion pairing effects on the electronic structure of unsupported uranium–arenide sandwich complexes. Issue 40 (17th September 2021) - Murillo, Jesse; Bhowmick, Rina; Harriman, Katie L. M.; Gomez-Torres, Alejandra; Wright, Joshua; Meulenberg, Robert W.; Miró, Pere; Metta-Magaña, Alejandro; Murugesu, Muralee; Vlaisavljevich, Bess; Fortier, Skye
Abstract : Use of Chatt metal-arene protocols with uranium leads to the synthesis of the first well-characterized, unsupported actinide–arenide sandwich complexes. The electronic structures of the actinide centres show a key sensitivity to ion pairing effects. Abstract : Addition of [UI2 (THF)3 (μ-OMe)]2 ·THF (2 ·THF) to THF solutions containing 6 equiv. of K[C14 H10 ] generates the heteroleptic dimeric complexes [K(18-crown-6)(THF)2 ]2 [U(η 6 -C14 H10 )(η 4 -C14 H10 )(μ-OMe)]2 ·4THF (1 18C6 ·4THF) and {[K(THF)3 ][U(η 6 -C14 H10 )(η 4 -C14 H10 )(μ-OMe)]}2 (1 THF ) upon crystallization of the products in THF in the presence or absence of 18-crown-6, respectively. Both 1 18C6 ·4THF and 1 THF are thermally stable in the solid-state at room temperature; however, after crystallization, they become insoluble in THF or DME solutions and instead gradually decompose upon standing. X-ray diffraction analysis reveals 1 18C6 ·4THF and 1 THF to be structurally similar, possessing uranium centres sandwiched between bent anthracenide ligands of mixed tetrahapto and hexahapto ligation modes. Yet, the two complexes are distinguished by the close contact potassium-arenide ion pairing that is seen in 1 THF but absent in 1 18C6 ·4THF, which is observed to have a significant effect on the electronic characteristics of the two complexes. Structural analysis, SQUID magnetometry data, XANES spectral characterization, and computational analyses are generally consistent with U(iv ) formal assignments for the metal centres in both 1 18C6 ·4THF and 1 THF, though noticeable differences are detected between the two species. For instance, the effective magnetic moment of 1 THF (3.74 μ B ) is significantly lower than that of 1 18C6 ·4THF (4.40 μ B ) at 300 K. Furthermore, the XANES data shows the U LIII -edge absorption energy for 1 THF to be 0.9 eV higher than that of 1 18C6 ·4THF, suggestive of more oxidized metal centres in the former. Of note, CASSCF calculations on the model complex {[U(η 6 -C14 H10 )(η 4 -C14 H10 )(μ-OMe)]2 } 2− (1* ) shows highly polarized uranium–arenide interactions defined by π-type bonds where the metal contributions are primarily comprised by the 6d-orbitals (7.3 ± 0.6%) with minor participation from the 5f-orbitals (1.5 ± 0.5%). These unique complexes provide new insights into actinide–arenide bonding interactions and show the sensitivity of the electronic structures of the uranium atoms to coordination sphere effects.